Sanshiy Travel Agency / Khairul Bashariah Abu Bakar... [et al.] - Abu Bakar, Khairul Bashariah; Abdul Wahid, Nurul Aida; Mohd Jali, Norizam; Abd Hamid, Nor Ashikin (2000)
Sanshiy Travel Agency was established on 11 June 2001 and the operation will start on 1 January 2002. This company Focuses on business activities in the form of travel services. They also prepare packages suitable for the customers as well as managing transportation and accommodation.